Global trends in surgical approach to neonatal brachial plexus palsy: a systematic review - Michael F. Levidy; Amanda Azer; Jasmine Shafei; Nivetha Srinivasan; Jasmine Mahajan; Shivani Gupta; George Abdelmalek; Krittika Pant; Kunj Jain; Yash Shah; Zheshi Zheng; Johnny Chuieng-Yi Lu; et al. (Frontiers in Surgery)
BackgroundWe analyzed trends in age at surgery and surgical approach over time and geography.MethodsWe performed a systematic review according to PRISMA-IPD guidelines to include individual patient data. Collected data included age at surgery, location of surgery, and surgical approach. The surgical approach was independently categorized as the exploration of the brachial plexus (EBP) or nerve transfer without root exploration (NTwoRE). EBP was defined as exploring the brachial plexus in the supraclavicular fossa and applying a choice of coaptation procedures. NTwoRE included those sourcing donor nerves from, or entirely occurring outside of the plexus without exploring the root of the brachial plexus.ResultsRegression analysis of age at surgery 1985–2020 showed that age at BPBI surgery is rising (p < 0.05). Surgery was performed at a younger age in patients from Europe (7.06 ± 7.77 months) and Asia (7.58 ± 5.33 months) than those from North America (10.44 ± 5.01 months) and South America (14.71 ± 4.53 months) (p < 0.05). NTwoRE was more common in North America (37%) and least common in Europe (12%). Age at EBP was 7.2 ± 5.77 months, and age at NTwoRE was 15.85 ± 13.18 months (p < 0.05). The incidence of NTwoRE is increasing time.ConclusionsAge at NBPP surgery is increasing over time. Regional differences exist in age at NBPP surgery. Approaches to NBPP surgery that avoid exploration of BP roots are becoming more popular. Age at EBP is lower than age at NTwoRE.